Epilepsy in adults with neurodevelopmental disability ‐ what every neurologist should know. Issue 1 (15th February 2022) - Watkins, Lance V.; Linehan, Christine; Brandt, Christian; Snoeijen‐Schouwenaars, Francesca; McGowan, Paula; Shankar, Rohit
Abstract: This seminar in epileptology addresses Learning Objective 6.1.4 of the International League against Epilepsy Curriculum: Demonstrate the ability to recognize and manage the special needs of persons with epilepsy (and Neurodevelopmental Disorders [NDDs]). The review identifies the essential competencies for neurologists working with people with epilepsy and NDDs, and these competencies are discussed alongside clinical examples. Furthermore, the seminar explores the opportunities offered by integrated service provision between neurology and services for NDD. The epileptic encephalopathies are not a subject of this seminar paper as they are circumscribed by other ILAE learning objectives. This seminar frames the complexity of seizures in association with NDD with a focus on major NDDs; intellectual disability, autism spectrum disorder, and attention deficit hyperactivity disorder. The evidence presented considers epidemiology, co‐morbidities, risk factors, mortality, and the diagnostic and treatment challenges. People with NDDs and epilepsy have higher rates of physical and psychiatric co‐morbidity, polypharmacy, neuropsychiatric side effects of drugs, and premature mortality including sudden unexpected death in epilepsy. There is a limited Level 1 evidence base to guide assessment and treatment for seizures in adults with NDDs. Therefore, throughout this seminar, the evidence presented for associations and treatment should be observed in context along with its limitations. The evidence for pharmacological treatment of seizures in association with NDDs is presented alongside expert commentary and guidance. There is Level 2 evidence to support treatment with some of the newer anti‐seizure medications including brivaracetam, lacosamide, eslicarbazepine acetate, and perampanel as second‐line choices. Seizures with a co‐morbid NDD should be considered as a collective complex clinical presentation and not discrete conditions. This seminar was co‐designed, co‐produced and co‐authored by an expert by experience and includes case studies and a video to highlight what can go wrong and how it can be avoided.